2018
DOI: 10.1016/j.mjafi.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for degenerative aortic valve disease in India: A case control study

Abstract: Background: Degenerative aortic valve disease often co-exists with coronary artery disease (CAD) and studies done in western populations have shown that it shares the same risk factors which cause CAD. However little is known in this context among Asian Indians. The current study looks into the risk factors of degenerative aortic valve disease in Asian Indian population. Methods: Ninety-one consecutive patients with severe aortic stenosis (AS) reporting for left heart catheterization prior to valve replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“… 12 The majority of patients with CAD do not develop aortic valve disease, despite the fact that atherosclerosis and CAVD have the same risk factors. 8 , 16 , 43 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 12 The majority of patients with CAD do not develop aortic valve disease, despite the fact that atherosclerosis and CAVD have the same risk factors. 8 , 16 , 43 …”
Section: Discussionmentioning
confidence: 99%
“…These findings are in contrast to those of the studies conducted by Ye et al, Chadha et al, Sathyamurthy, and Picardo et al, who reported no significant association between aortic valve sclerosis and hypertension. 8,27,39,42 Vascular Health and Risk Management 2022:18 https://doi.org/10.2147/VHRM.S376955…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk factors involved in the development of aortic valve sclerosis were similar to that in the development of vascular atherosclerosis, including ageing, gender, hypertension, smoking, hyperlipidaemia, diabetes. 7–9 Though many studies had reported a significant association between DAVD and risk of concomitant coronary artery disease, 9 10 most of them were cross-sectional or retrospective studies, which limited their ability to infer the possible causal relationship. Moreover, some previous studies were hospital-based and only enrolled patients undergoing valve replacement treatment for severe VHDs.…”
Section: Introductionmentioning
confidence: 99%